Berbagai Faktor yang Mempengaruhi Saving Behavior K-Pop Fans di Bandung - Arsytania, Raden Arvi; Setyawan, Surya (Direktorat Riset dan Pengabdian kepada Masyarakat Universitas Bina Darma, 2024)
K-pop fans have become one of the most loyal communities in Indonesia, purchasing anything to support their idols. Saving behavior has become a common habit among K-pop fans. This study aims to analyze whether financial literacy, subjective norms, and control influence saving behavior mediated by saving intention among K-Pop fans residing in Bandung. Primary data was collected using an online Likert scale questionnaire. The sample size was determined using probability sampling techniques based on Lemmeshow, amounting to 100 K-Pop fans. The data was analyzed using path analysis with the SPSS application. The results of this study show that subjective norms have a positive effect on saving intention, while financial literacy and locus of control do not have an impact. Saving intention influences saving behavior. Financial literacy and locus of control influence saving behavior mediated by saving intention, whereas subjective norm does not have an effect. The results of this study suggest that K-pop fans in Bandung should improve their financial literacy and pay attention to subjective norms and locus of control to foster saving intention and enhance their saving behavior. Keywords: Financial Literacy, Subjective Norm, Locus of Control, Saving Behavior, Saving intention. Abstrak K-Pop fans menjadi salah satu komunitas di Indonesia yang sangat loyal dengan membeli apapun untuk mendukung idolanya. Perilaku menabung menjadi salah satu kebiasaan seorang K-Pop fans. Penelitian ini memiliki tujuan untuk menganalisis apakah terdapat pengaruh financial literacy, subjective norm, dan locus of control terhadap saving behavior yang dimediasi oleh saving intention pada K-Pop fans yang berdomisili di Bandung. Pengambilan data primer menggunakan kuesioner online skala likert. Jumlah sampel ditentukan berdasarkan Lemmeshow sebanyak 100 K-Pop fans dengan teknik purposive sampling. Data dianalisis dengan menggunakan analisis jalur dengan aplikasi SPSS. Hasil dari penelitian ini yaitu subjective norm berpengaruh positif terhadap saving intention sedangkan financial literacy dan locus of control tidak mempengaruhi, saving intention berpengaruh terhadap saving behavior, financial literacy dan locus of control mempengaruhi saving behavior yang dimediasi saving intention sedangkan subjective norm tidak. Hasil penelitian ini memiliki saran kepada K-Pop fans di Bandung untuk meningkatkan financial literacy, memperhatikan subjective norm dan locus of control untuk dapat menumbuhkan saving intention dan meningkatkan saving behavior pada mereka. Kata kunci: Financial Literacy, Subjective Norm, Locus Of Control, Saving Behavior, Saving Intention